Conceptualization of economic development in the paradigm of the modern economic system - Chоrnоdоn, V.І. (Економічний вісник Донбасу, 2010)
The work defines the conceptual basis for economic development, especially the formation of the economic system under contemporary conditions based innovation component of transformational processes, factors that influence the creation of competitive economy. Key words: economic system, development of innovative models, competitive economy.